Down-Regulation of miR-7 in Gastric Cancer Is Associated With Elevated LDH-A Expression and Chemoresistance to Cisplatin - Jin, Hui-Fang; Wang, Ju-Feng; Shao, Ming; Zhou, Kailu; Ma, Xiao; Lv, Xian-Ping (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs (miRNAs) are dysregulated in the context of many cancer types, making them potentially ideal diagnostic or therapeutic targets in patients in which they are aberrantly expressed. In the present study, we found miR-7 to be downregulated in gastric cancer (GC), and we further determined its expression to be closely linked to GC sensitivity to the chemotherapeutic compound cisplatin. This effect appears to be at least partially attributable to the regulation of LDH-A, which is a miR-7 target gene and expression of LDH-A is negatively correlated with miR-7 expression in primary GC tumor samples. When upregulated, we also determined that miR-7 was able to inhibit the proliferation, colony formation, and glycolysis of GC cells owing to its regulation of LDH-A. Moreover, overexpression of miR-7 render cells more sensitive to cisplatin. Our results thus provide novel evidence that miR-7 is a key mediator of GC growth and chemosensitivity through its regulation of LDH-A, thus potentially highlighting this pathway as a therapeutic target for treating affected patients.